O estágio supervisionado sob a perspectiva dos formandos do curso de licenciatura em ciências naturais - SILVA, Werlen (2024)
The work aims to analyze the conceptions of graduates of the Licentiate Degree in Natural Sciences, at the Federal University of Pará, Tocantins-Cametá campus, Oeiras do Pará pole, regarding their academic training under the Supervised Internship. For this, we resorted to the qualitative research approach (BOGDAN; BIKLEN, 1994), and the foundations of descriptive research (GIL, 2008). For data collection we used the collective interview technique “Focal Group” (GATTI, 2005), with eleven trainees, analyzed from the perspective of Textual Discursive Analysis (MORAES, 2003). Future Science teachers highlight the importance of the internship in their formative trajectories and the difficulty encountered in discerning teaching theories in practice. Most of the interns' conceptions are linked to the internship view as the practical part of training. They confessed some difficulties they had during the processes, which reveal insecurity in their teaching practices. However, it is noteworthy that they have a reflective sense, something necessary for pedagogical actions. The internship is a great ally for science graduates, given that science education is democratically linked to the development of critical citizens, teaching must consist of inter and multidisciplinary activities, the teacher has a fundamental role to consolidate these perspectives.